Generating Trips and Assigning Route to a SUMO Network Through the Origin–Destination Matrix: A Case Study of Mobility Routing Model for VANETs. Issue 4 (4th July 2022) - Bhatia, Tarandeep Kaur; Ramachandran, Ramkumar Ketti; Doss, Robin; Pan, Lei
Abstract : Vehicular Ad-hoc NETworks (VANETs) is an important research domain as it deals with the safety of vehicles moving on roads. The selection of the most prominent routing protocol in this field is a challenging job due to the high mobility rate of VANETs. The foremost motive for writing this paper is to recognize the most suitable protocol that can be used for a high-density traffic region. Therefore, the evaluation of six popular routing protocols (AODV, DSDV, DSR, GPSR, OLSR, and ZRP) of VANETs is examined in the congested city of Delhi. For this, a methodology is being presented that explains the creation of a network using the SUMO tool and assigning a trip and route to the obtained network through the Origin-Destination matrix. Then, by adopting the created network file, the TCL File and NAM File are generated using the NS-2. Finally, selected protocols' performance is examined and evaluated based on the metrics such as Throughput, Packet Delivery Ratio (PDR), Delay, Packet Loss Ratio (PLR), and Routing Overhead. The results showed that the AODV protocol acts as an appropriate routing protocol and could perform better with our presented approach. Also, the comparison is conducted with the results obtained for the AODV routing protocol using the presented approach and the existing approaches. The comparison results depict that the AODV routing protocol presents much better results by using the presented methodology than by using the existing methods in terms of throughput, delay, and PDR.